(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
The Malayalam month of Karkidaka fall during monsoons rather classically known as the Varsha ritu (July-August). Kerala is a hub of unique healthcare practises. One such practice is the “Karkidaka Chikitsa” which includes both internal and external medications taken during the month. Karkidaka Kanji fondly known as Oushadha Kanji is a medicated gruel, either consumed along with these treatments or alone during this period. In Varsha ritu, there will be decreased Jatharagni and Sharira bala. Hence the seasonal adaptations are carried out for Tridosha shamana and Deepana. This maybe the principle behind adopting Karkidaka Kanji by traditional practitioners of Kerala. In the present study details of the recipe was collected form among the traditional practitioners, Ayurvedic doctors of Kerala and the results were tabulated. An in depth literature survey was done for analysing the properties of the medicines used in the preparation. The analysis showed that this is an example of ritucharya modified according to Desa and Satmya. This study highlights the importance of documenting the ethnic practises for further reference.